Reframing occupational safety culture through dharma: lessons from the Ramayana - Neupane, Khagendra (International Journal of Occupational Safety and Health, 2026)
Introduction: Occupational safety culture is conventionally understood through technical systems, regulations, and management structures. However, ethical values hold a key role in shaping human behavior, responsibility, and risk- related decision-making in workplaces. The Ramayana, a classical epic of the East, foregrounds the concept of dharma-moral duty, righteousness and responsibility, offering a rich moral framework that can inform contemporary approaches to occupational safety. This conceptual paper examines how the principles of workplace ethics and duty (dharma), as articulated in the Ramayana, can contribute to a deeper understanding of contemporary occupational safety culture. It aims to develop an integrative conceptual model that connects ancient moral philosophy with contemporary safety paradigms. Methods: The study employs qualitative textual analysis of the epic’s major episodes and characters. It focuses on duty, leadership, protection of the weak, worker responsibility, and ethical decision-making. These themes are then linked to modern occupational safety culture constructs, such as leadership commitment, worker participation and protection of vulnerable groups, using a narrative synthesis approach. Results: The Ramayana illustrates multiple ethical responsibilities. Rama, the protagonist, as the perfect ruler, promotes collective welfare. Lakshmana, Hanuman, and the Vanara Sena, as devoted workers, accept responsibility. Sita’s trials focus on the importance of systems that protect vulnerable individuals. Vibhishana’s moral dissent exemplifies the courage to stand against unethical practices. From these narratives, a Dharma-based safety culture framework is derived, highlighting (1) ethical leadership that protects workers, (2) worker duty and solidarity, (3) institutional protection of vulnerable groups, and (4) moral decision-making under risk. Conclusion: Integrating dharma principles into occupational safety culture provides a complementary ethical foundation for technical and regulatory systems. Future empirical studies can validate and operationalize this framework in workplace settings.